Carbon Market Governance for Greenhouse Gas Mitigation in Vietnam: Legal Insights from the European Union - Tran, Ngoc Minh; Ha, Hoa Thanh (Faculty of Law, Jambi University, 2026)
This study analyzes the emergent carbon market of Vietnam from the perspective of legal governance rather than the traditional view of greenhouse gas mitigating policy. It hypothesizes that the trading of carbon units would be ineffective without the law’s ability to create credible scarcity, provide a reliable emissions data, secure carbon units, manage the trading activities, and govern the law’s compliance. The study uses qualitative legal research, doctrinal analysis, and comparative law as well as case-study methodology to evaluate the recent legal acts of Vietnam, including the Law and decrees on Environmental Protection. Methodologically, it aims to gather insights based on the European Union Emissions Trading System (EU ETS), specifically regarding cap-setting, allowance allocation, monitoring, reporting, verification and registry governance, along with market stability, leakage effect, and trading safety. The study determines that Vietnam has advanced significantly beyond mere legal recognition, and has implemented the initial design of a trading system. However, a number of governance issues remain, such as institutional fragmentation, poor transparency and protection, and unregulated market manipulation as well as the risk of double-counting. Its principal legal contribution is a governance-function framework demonstrating that Vietnam is expected to adapt, rather than replicate, the EU ETS by strengthening legal certainty, market integrity, institutional coordination, and compatibility with international carbon-market rules